Demand heterogeneity in insurance markets: Implications for equity and efficiency - Michael Geruso (Quantitative Economics, 2017)
In many markets insurers are barred from price discrimination based on con- sumer characteristics like age, gender, and medical history. In this paper, I build on a recent literature to show why such policies are inefficient if consumers differ in their willingness-to-pay for insurance conditional on the insured losses they generate. Using administrative claims data, I then show that this type of demand heterogeneity is empirically relevant in a consumer health plan setting. Younger and older consumers and men and women reveal strikingly different demand for health insurance, conditional on their objective medical spending risk. This implies that these groups must face different prices so as to sort themselves efficiently across insurance contracts. The theoretical and empirical analysis highlights a fundamental trade-off between equity and efficiency that is unique to selection markets.
Keywords: D82; I11; I13; I18; 330; Community rating; adverse selection; demand heterogeneity; Versicherungsbeitrag; Preisdifferenzierung; Versicherungsmarkt; Nachfrage; Zahlungsbereitschaftsanalyse; Präferenztheorie; Adverse Selektion; Gerechtigkeit; Wohlfahrtsanalyse; Theorie; Krankenversicherung; Betriebliche Sozialleistungen; USA